EFFECT OF NB2O5 ALLOYING ON THERMAL-EXPANSION ANISOTROPY OF 2 MOL-PERCENT Y2O3-STABILIZED TETRAGONAL ZRO2 - KIM, DJ; BECHER, PF; HUBBARD, CR (AMER CERAMIC SOC, 1993)
Tetragonal ZrO2 (t-ZrO2) solid solutions were prepared with additions of 2 mol% Y2O3 plus up to 0.45 mol% Nb2O5. The thermal expansion coefficients in both the a- and c-axis lattice directions increased with Nb2O5 alloying and the thermal expansion in the c-axis direction was greater than that in the a-axis direction over the entire composition range. This anisotropic thermal expansion behavior was related to the 4-fold coordination of Nb5+ with oxygen ions in t-ZrO2, solid solutions in the system ZrO2-Y2O3-Nb2O5. The fracture toughness continuously increased with Nb2O5 alloying and suggested that the c/a axial ratio is a more significant factor than the internal stress that arises from the thermal expansion anisotropy, in the determination of the transformability of t-ZrO2 in this system.
Keywords: MARTENSITIC-TRANSFORMATION; FRACTURE-TOUGHNESS; ZIRCONIA; TEMPERATURE